2016
DOI: 10.1002/2015ja021862
|View full text |Cite
|
Sign up to set email alerts
|

High‐spatial‐resolution velocity measurements derived using Local Divergence‐Free Fitting of SuperDARN observations

Abstract: A new technique for analysis of Super Dual Auroral Radar Network (SuperDARN) line‐of‐sight velocity observations enables resolving plasma convection with unprecedented spatial resolution. The technique, Local Divergence‐Free Fitting (LDFF), can be used to produce maps with a spatial resolution that is determined by the resolution of the observations rather than an arbitrary fit order. Other techniques, which express the potential as a sum of harmonic functions, limit the number of functions in the expansion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 23 publications
(31 reference statements)
3
55
0
Order By: Relevance
“…The ion distributions in Fig. 2k show a distorted D-shaped distribution similar to the finding of Broll et al (2017). The distortion is due to particles traveling in the field-aligned direction from the reconnection site to a stronger magnetic field region, and Broll et al (2017) estimated the traveling distance to be a few Re for the observed level of distortion.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…The ion distributions in Fig. 2k show a distorted D-shaped distribution similar to the finding of Broll et al (2017). The distortion is due to particles traveling in the field-aligned direction from the reconnection site to a stronger magnetic field region, and Broll et al (2017) estimated the traveling distance to be a few Re for the observed level of distortion.…”
Section: Methodssupporting
confidence: 60%
“…The transmitted ions have a cutoff parallel velocity (i.e., de Hoffmann-Teller velocity) below which no ions could enter the magnetosphere. The D-shaped ion distributions are deformed into a crescent shape as ions travel away from the reconnection site (Broll et al, 2017). We require the satellites to operate in the fast survey or burst mode in which ion distributions are available at 3 s resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Fast plasma flows (up to 1000s of m/s) in the polar cap have been observed in both coherent and incoherent scatter radar measurements prior to the activation of a PBI Bristow et al 2016). Figure 3 shows and example event from Nishimura et al (2010b).…”
Section: Drivers/causesmentioning
confidence: 98%
“…Initial tests of the local‐divergence‐free‐fitting technique (Bristow et al, ) using the image data illustrate the promise of these observations. Figure shows the estimated vector field for 0102 UT on 26 August 2018, which corresponds to frame “b” of Figure .…”
Section: Flow Field Reconstruction Using Image Datamentioning
confidence: 89%